ANALISIS FAKTOR RISIKO PADA PROYEK KONSTRUKSI GEDUNG - Rafly Edriandaya; Ely Mulyati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: Construction projects are inseparable from various risks that may affect project performance. This study aims to analyze the factors influencing construction risk using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach. The research examines nine independent variables, namely force majeure, material, equipment, labor, construction, contractual, design and technology, management, and environmental impact, on construction risk factors. Data were collected through questionnaires distributed to respondents involved in construction projects. The analysis results indicate that material, equipment, labor, and management variables have a direct influence on construction risk factors, while force majeure, construction, contractual, design and technology, and environmental impact do not show significant effects. These findings suggest that effective management and proper resource control play a crucial role in minimizing construction risks. The results of this study are expected to contribute to improving risk management strategies in construction projects.Keywords: Construction risk, PLS-SEM, project management, construction factors, risk analysis.